2019
DOI: 10.3390/su11020303
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Integration of Pakistan with Its Trading Partners: A Multivariate DCC-GARCH Model Approach

Abstract: A decade after the global financial crisis, the developments in stock market integration have increased the stability and liquidity of markets, and decreased the diversification benefits for investors. International trade is an important determinant of stock market interdependence. The objective of this study is to analyze the co-movements and the portfolio diversification between the stock markets of Pakistan and its top trading partners, namely China, Indonesia, Malaysia, the United Kingdom, and the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…The results of the preliminary analysis also showed that there are co-movement patterns of higher frequencies during the crisis's periods of 1997, 2008, and 2015. The closeness among the stock markets considered economies show that the crisis period converged the economies reducing the differentials of the return on the stock markets of the Asian emerging economies as found by [4]. The closeness of the stock market movements show the integration of the stock markets thus bringing these economies closer.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…The results of the preliminary analysis also showed that there are co-movement patterns of higher frequencies during the crisis's periods of 1997, 2008, and 2015. The closeness among the stock markets considered economies show that the crisis period converged the economies reducing the differentials of the return on the stock markets of the Asian emerging economies as found by [4]. The closeness of the stock market movements show the integration of the stock markets thus bringing these economies closer.…”
Section: Discussionmentioning
confidence: 71%
“…There has been burgeoning research on the stock market linkage to understand the market behavior and the investment opportunities using stock market data. The past researchers have used different tools like Correlation coefficient, GARCH models, and Copula models [79]. Besides these models, Wavelet model has proved an appropriate alternative to other time series models.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, there have been many studies to obtain the strategy for sustainable and effective portfolio selection with various approaches [20][21][22][23]. In this paper, a well-established benchmark (e.g., Dow 30 index), which offers sustainable and stable risk-return profiles with low costs, is used to propose an effective strategy for constructing a portfolio.…”
Section: Literature Reviewsmentioning
confidence: 99%